Masjid dan Musala dalam Sorotan: Kajian Sosiopragmatik Kesalahan Nama Masjid/ Musala di Padang - Hadi, Syofyan; Faisol, Yufni; Wartiman, Wartiman (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2019)
This study is an extension research of previous research finding conducted by researcher and team, which resulted in more than 50 names of mosques and musalas in Padang were considered error. These forms of error exist in terms of morphological, semantic, morphology and semantic contexts and imla’ rules. However, to explain these errors more comprehensively, a sociopragmatic viewpoint is required. In this context, it can be assumed that in understanding a word or language, the sociological context of the speaker and its use in determining and choosing certain symbols in their language are necessary to be considered. The phenomenon of naming a house of worship such as a mosque and musala cannot be separated from social context of the owners of the place of worship. This frequently causes pragmalinguistic failure in understanding the phenomenon of language which only relies on how to express language structurally, following the rules exclusively without giving attention to the social and cultural context of the speaker itself. This research is a field research which applies qualitative methods. The main data is obtained through interviews with mosques and musalas administrator and also the surrounding community to find out the historical and socio-cultural background of naming the mosques or musalas. The data of this study are all the names of mosques and musalas in Padang, especially those 50 names that are considered error from the perspective of Arabic grammar.Keywords: Sociopragmatics, mosque, musala, Padang Kajian ini adalah kelanjutan dari temuan peneliti dan tim yang dalam penelitian sebelumnya mendapatkan kesalahan pada lebih dari 50 nama masjid dan musala yang ada di kota Padang. Bentuk-bentuk kesalahan tersebut ada dalam konteks morfologis, semantic, morfologis dan semantic serta kaidah imlai’. Akan tetapi, untuk menjelaskan kesalahan tersebut secara lebih komprehensif diperlukan sudut pandang sosiopragmatik. Dalam konteks ini bisa dipahami bahwa pemahaman sebuah kata atau bahasa haruslah memperhatikan konteks sosiologis penutur dan penggunanya dalam menentukan dan memilih simbol tertentu dalam bahasa mereka. Tidak terkecuali tentunya penamaan sebuah rumah ibadah seperti masjid dan musala yang juga tidak bisa dilepaskan dari konteks sosial masyarakat yang menjadi pemilik rumah ibadah tersebut. Hal ini yang seringkali menjadi penyebab kegagalan pragmalinguistik dalam memahami fenomena bahasa yang hanya bertumpu pada bagaimana mengungkapkan bahasa sesuai aturan tanpa memberikan perhatian kepada koteks sosial dan cultural penutur itu sendiri. Penelitian ini adalah penelitian lapangan (field research) dengan menggunakan metode kualitatif, di mana data utama diperoleh melalui wawancara dengan pengurus masjid dan musala dan juga masyarakat sekitar untuk mengetahui latar belakang historis dan sosio-budaya penamaan masjid atau musala mereka. Adapun data penelitian ini adalah semua nama masjid dan musala yang ada di kota Padang, khususnya yang dianggap keliru dalam sudut pandang tata bahasa Arab yaitu kurang lebih 50 masjid dan musala.Kata Kunci: Sosiopragmatik, Masjid, Musala, Padang